Study on the efect of oligoalginate on some nutritive composition of Tetreselmis sp. used to feed larvae of Babylonia aerolata - Huong, Vo Thi Mai (Academia Journal of Biology, 2012)
Tetraselmis sp. is a commonly used marine alga in aquaculture. It contains high quality of lipid, unsaturated acid, protein and amino acid.... Oligoalginate (OA) is a biological product of Sargassum. It increases some nutritive properties of Tetraselmis sp. In range of OA 60-140 mg/l, lipid contents increase 8.3-10.4% and and amino acid contents increase 12.48% in comparing to the control. The OA of 80-100 mg/l has the most effect for Tetraselmis sp. When the larvae Veliger of Babylonia aerolata was fed by Tetraselmis sp. that was cultured in medium with OA, they grew better. The larvae’s size was bigger and the rate of larvae changing into stage Juvenile was higher than that fed by Tetraselmis sp. cultured in the control condition.